Legal Protection for Micro, Small, and Medium Enterprises in Aceh: Conflict between the Banking Law and the Qanun on Islamic Financial Institutions - Yusri, Yusri; Fahmi, Chairul; Muazzin, Muazzin; Fitri, Ria; Rasyid, Laila Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study aims to analyze legal protection for Micro, Small, and Medium Enterprises (MSMEs) in Aceh Province amidst the contestation between the National Banking Law, the Qanun on Sharia Financial Institutions (LKS), and the obligation to halal certification. Since the enactment of Aceh Qanun Number 11 of 2018, the banking system in Aceh has undergone a total transformation towards sharia, which has created challenges in capital accessibility and regulatory harmonization. On the other hand, the Halal Product Guarantee Law requires certification for all MSME products, with a transition deadline for micro-enterprises until 2026. This study uses empirical legal methods, analyzed with the theory of asymmetric autonomy and legal pluralism. Data were collected by referring to document studies and in-depth interviews. The study concludes that legal protection is needed for MSMEs in Aceh, which still face structural obstacles due to disharmony between central and regional regulations and limited sharia-supporting infrastructure. Therefore, from the perspective of the theory of asymmetric autonomy, it provides space for the formation of regulations tailored to the sociological and philosophical characteristics of the Islamic-based Acehnese society. Legal pluralism also makes it possible to harmonize state law, Islamic law and customary law so that they can live side by side de facto and de jure. The research recommends strengthening the operational technical regulations of the Qanun LKS and integrating the halal industry ecosystem through a more inclusive Sharia People's Business Credit (KUR) financing scheme to ensure the economic sustainability of the Acehnese people.